2018
DOI: 10.5565/publmat6211805
|View full text |Cite
|
Sign up to set email alerts
|

Stability of generalized linear Weingarten hypersurfaces immersed in the Euclidean space

Abstract: Given a positive function F defined on the unit Euclidean sphere and satisfying a suitable convexity condition, we consider, for hypersurfaces M n immersed in the Euclidean space R n+1 , the so-called k-th anisotropic mean curvatures H F k , 0 ≤ k ≤ n. For fixed 0 ≤ r ≤ s ≤ n, a hypersurface M n of R n+1 is said to be (r, s, F )-linear Weingarten when its k-th anisotropic mean curvatures H F k , r ≤ k ≤ s, are linearly related. In this setting, we establish the concept of stability concerning closed (r, s, F )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Many of the classical characterizations of the geodesic hyperspheres have an analogue with the Wulff Shape as characteristic hypersurface, like anisotropic Hopf or Alexandrovtype theorems (see [14,15,16,18,19,20,23]). In [12], da Silva, de Lima and Velásquez gave an anisotropic analogue to their results in [11] and recover as particular cases the results of [6], [15] and [20]. This gives another characterization of the Wulff shape as the only hypersurface (up to translations and homotheties) which have linearly related anisotropic mean curvatures, without assuming that X(M ) is convex or embedded.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Many of the classical characterizations of the geodesic hyperspheres have an analogue with the Wulff Shape as characteristic hypersurface, like anisotropic Hopf or Alexandrovtype theorems (see [14,15,16,18,19,20,23]). In [12], da Silva, de Lima and Velásquez gave an anisotropic analogue to their results in [11] and recover as particular cases the results of [6], [15] and [20]. This gives another characterization of the Wulff shape as the only hypersurface (up to translations and homotheties) which have linearly related anisotropic mean curvatures, without assuming that X(M ) is convex or embedded.…”
Section: Introductionmentioning
confidence: 55%
“…This gives another characterization of the Wulff shape as the only hypersurface (up to translations and homotheties) which have linearly related anisotropic mean curvatures, without assuming that X(M ) is convex or embedded. In the present note, we prove that the result of da Silva, de Lima and Velásquez in [12] can be improved with a weaker assumption, namely with almost (r, s, F )stability. Precisely, we prove the following: Theorem 1.1.…”
Section: Introductionmentioning
confidence: 56%
“…, n − 1} are just the hypersurfaces having constant (r + 1)-th mean curvature H r+1 . In recent years, several papers have been published showing the interest in understanding the geometry of the (r, s)-linear Weingarten hypersurfaces (see [2,3,14,15,23]). For instance, we can highlight that the author jointly with H. de Lima and A. de Sousa showed in [23, Section 3] that (r, s)-linear Weingarten closed hypersurfaces compact are critical points of the variational problem of minimizing a suitable linear combination…”
Section: And (Cf [22 Teorema 2])mentioning
confidence: 99%
“…Taking into account the relation between H 2 and the normalized scalar curvature R given in (2.4), we observe from (2.10) that the (0, 1)-linear Weingarten hypersurfaces x : Σ n ↬ S n+1 are called simply linear Weingarten hypersurfaces, and there is a vast recent literature treating the problem of characterizing these hypersurfaces (see, for instance, [5,6,7,12,16,17,18]). It is because of this observation that the hypersurfaces described in Definition 2.1 are also called, in the current literature, the generalized linear Weingarten hypersurfaces (see [2,3,14,15,23]). Furthermore, when r = s ∈ {0, .…”
Section: And (Cf [22 Teorema 2])mentioning
confidence: 99%
“…and some restricted a, b must be the Wulff shape. In 2018, da Silva et al [DDV18] showed that if there exist nonnegative real numbers…”
Section: Introductionmentioning
confidence: 99%